The 2016 Scottish Parliament Elections: Unionist Parties and the Constitutional Divide - Fiona Simpkins (Revue Française de Civilisation Britannique)
If voting for the Conservative party had become somewhat of a rarity in Scotland since the Thatcher era, the May 2016 Scottish Parliament election ushered in a new era, as it saw the resurgence of the Scottish Conservatives after they obtained a total of 31 seats. A comparative perspective on Labour and Conservative Party attitudes to devolution and post-devolution Scottish politics will shed light on the electoral demise of the former and the rising fortunes of the latter. This article seeks to examine the main unionist parties’ differences in terms of structural and ideological adaptation to devolution within the broad centre-left consensus that characterizes the current Scottish political landscape.